Study of Local Herb Potency as Rumen Modifier: Red Ginger (Zingiber Officinale Var. Rubrum) Addition Effect on In Vitro Ruminal Nutrient Digestibility - Kurniawati, Asih; Yusiati, Lies Mira; Widodo, Widodo; Artama, Wayan Tunas (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
Red ginger is herb that commonly used as part of traditional medicine due to its essential oil content. Some essential oil have proven as rumen fermentation modifier. Addition of red ginger in ruminant diet was studied using in vitro gas production technique to evaluate its effect on nutrient digestibility. Red ginger meal was added to meet essential oil level in fermentation medium of 0 mg/l as control, 25, 50, 75 and 100 mg/l. The diet consisted of Penisetum hybride, rice bran, wheat pollard in ratio 60:20:20 DM basis. Feed fermentation was incubated for 24 h at 39Â°C. At the end of incubation data of gas production volume was taken, and residual feed were collected for further nutrient analysis to calculate the digestibility of dry matter (DM), organic matter (OM), crude protein (CP) and crude fiber (CF). Variance analysis was used to analysis collected data, followed by DMRT analysis.Â Addition of red ginger increase total volume of gas production at level 50 mg/L and above. DM and OM digestibility did not affected by red ginger addition whereas CP digestibility were significantly decreased start at level 50 mg/l. In contrast, CF digestibility of treatment level of 50 mg/l significantly higher than control. In conclusion, addition of red ginger correspond to level essential oil of 50 to 100 mg/l improve ruminal nutrient fermentation.